PERFORMANCE OF MASHBEAN INTERCROPPED IN COTTON PLANTED IN DIFFERENT PLANTING PATTERNS - Khan, Muhammad Bismillah; Khaliq, Abdul; Ahmad, Shakeel (Journal of Research (Science), 2004)
Performance of mashbean as intercrop in cotton was studied at the Agronomic Research Area University of Agriculture, Faisalabad (Pakistan) during the years 1996-97 and 1997-98. Cotton variety NIAB 78 was planted in 80-cm apart single rows and 120-cm spaced double row strips. Experiment was laid out in a RCBD with four replications. Net plot size was 7 m x 4.8 m. Mashbean was sown as intercrop in the space between 80-cm apart single rows as well as 120-cm spaced double row strips. Mashbean was also sown as a sole crop (P3). The intercrops produced substantially smaller yields when grown in association with cotton in either planting pattern compared to the sole crop yields. However, additional produce obtained from intercrop compensated the losses in cotton production. Intercropping of mashbean, in 120-cm apart double row strips of cotton proved to be feasible as well as convenient for farm operations.